Influence of interplanetary magnetic field and solar wind on auroral brightness in different regions. Issue 1 (31st January 2013) - Yang, Y. F.; Lu, J. Y.; Wang, J.‐S.; Peng, Z.; Zhou, L.
Abstract: [1] By integrating and averaging the auroral brightness from Polar Ultraviolet Imager auroral images, which have the whole auroral ovals, and combining the observation data of interplanetary magnetic field (IMF) and solar wind from NASA Operating Missions as a Node on the Internet (OMNI), we investigate the influence of IMF and solar wind on auroral activities, and analyze the separate roles of the solar wind dynamic pressure, density, and velocity on aurora, respectively. We statistically analyze the relations between the interplanetary conditions and the auroral brightness in dawnside, dayside, duskside, and nightside. It is found that the three components of the IMF have different effects on the auroral brightness in the different regions. Different from the nightside auroral brightness, the dawnside, dayside, and duskside auroral brightness are affected by the IMF B x, and B y components more significantly. The IMF B x and B y components have different effects on these three regional auroral brightness under the opposite polarities of the IMF B z . As expected, the nightside aurora is mainly affected by the IMF B z, and under southward IMF, the larger the | B z |, the brighter the nightside aurora. The IMF B x and B y components have no visible effects. On the other hand, it is also found that the aurora is not intensified singly with the increase of the solar wind dynamic pressure: when only the dynamic pressure is high, but the solar wind velocity is not very fast, the aurora will not necessarily be intensified significantly. These results can be used to qualitatively predict the auroral activities in different regions for various interplanetary conditions. Key Points: investigate the influence of IMF and solar wind on auroral activities the three components of the IMF have different effects on the auroral brightness the aurora is not intensified singly with the increase of SW dynamic pressure